Tradisi Sedekah Serabi yang ada di Kabupaten Empat Lawang - Cendy Lestari; Hudaidah Hudaidah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Sedekah Serabi tradition is one of the cultural heritages that developed in Empat Lawang Regency, South Sumatra Province. This tradition reflects a combination of local wisdom, religious values, and community togetherness. Historically, Sedekah Serabi is rooted in the tradition of post-harvest thanksgiving carried out by agrarian communities as a form of gratitude to God Almighty for the abundant crops. In its implementation, the community collectively makes serabi cakes and then donates them to neighbors, relatives, and children as a symbol of sharing sustenance and strengthening friendship. Over time, this tradition has not only become a form of thanksgiving, but has also developed into an annual cultural event that strengthens social identity and solidarity between residents. This study aims to explore the history, cultural values, and role of the Sedekah Serabi tradition in building social cohesion amid the dynamics of modern society.